A review on mercury in coal combustion process: Content and occurrence forms in coal, transformation, sampling methods, emission and control technologies. (July 2019) - Zhao, Shilin; Pudasainee, Deepak; Duan, Yufeng; Gupta, Rajender; Liu, Meng; Lu, Jianhong
Abstract: Mercury, as a global pollutant, has raised worldwide concern due to its high toxicity, long-distance transport, persistence, and bioaccumulation in the environment. Coal-fired power plants (CFPPs) are considered as the major anthropogenic mercury emission source to the atmosphere, especially for China, India, and the US. Studies on mercury in coal combustion process have been carried out for decades, which include content and occurrence forms of mercury in coal, mercury transformation during coal combustion, sampling, co-removal and emission of mercury in CFPPs, mercury removal technologies for CFPPs. This current review summarizes the knowledge and research developments concerning these mercury-related issues, and hopes to provide a comprehensive understanding of mercury in coal combustion process and guidance for future mercury research directions. The average mercury content in the coal from China, the US, and South Africa is 0.20, 0.17, and 0.20 mg/kg, respectively, which is higher than the world's coal average value of 0.1 mg/kg. In general, mercury in coal is in the forms of sulfide-bound mercury (mainly pyritic mercury, dominant), clay-bound mercury, and organic matter-bound mercury, which are influenced by diagenetic, coalification, and post-diagenetic conditions, etc. Mercury transformation in coal combustion includes homogeneous (without fly ash) and heterogeneous (with fly ash) reaction. The transformation is affected by the coal types, flue gas components, flue gas temperature, combustion atmosphere, coal ash properties, etc. The effects of chlorine, NOx, SO2, H2 O, O2 NH3 on elemental mercury (Hg 0 ) homogeneous oxidation and the influence of physical structure properties, unburned carbon, and metal oxides in fly ash as well as flue gas components on Hg 0 heterogeneous transformation are systematically reviewed in detail. For the mercury transformation in oxy-coal combustion, O2 promotes Hg 0 oxidation with Cl2 while NO and CO2 inhibit or do not favor that reaction. CO2 increases Hg 0 oxidation in the atmosphere of NO and N2 . SO2 will limit Hg 0 oxidation, while HCl has a higher oxidation effect on Hg 0 than that in air-coal combustion atmosphere. Fly ash plays an important role in Hg 0 oxidation. SO3 inhibits mercury retention by fly ash while H2 O promotes the oxidation. The sampling or analysis principle, sampling requirements, and advantages and disadvantages of the commonly used on-site mercury sampling methods, namely, Ontarion Hydro Method (OHM), US EPA Method 30B, and Hg-CEMS, are compared. The air pollution control devices (APCDs) in CFPPs also have the mercury co-removal ability besides the conventional pollutants, such as NOx, particulate matter (PM), SO2, and fine PM. Selective catalytic reduction (SCR) equipment, electrostatic precipitator (ESP) or fabric filter (FF), and wet flue gas desulfurization (WFGD) device are good at Hg 0 oxidation, particulate mercury (Hg p ) removal, and oxidized mercury (Hg 2+ ) capture, respectively. The Hg 0 oxidation rate for SCR equipment, and the total mercury (Hg t, Hg t = Hg 0 + Hg 2+ + Hg p ) removal rate for ESP, FF, and WFGD device is 6.5–79.9%, 11.5–90.4%, 28.5–90%, and 3.9–72%, respectively. Wet electrostatic precipitator (WESP) can capture Hg 0, Hg 2+, and Hg p simultaneously. The mercury transformation process in SCR, ESP, FF, WFGD, and WESP is also discussed. Hg t removal in ESP+WFGD, SCR+ESP+WFGD, SCR+ESP+FF+WFGD, and SCR+ESP+WFGD+WESP is 35.5–84%, 43.8–94.9%, 58.78–73.32%, and 56.59–89.07%, respectively. The mercury emission concentration in the reviewed CFPPs of China, South Korea, Poland, the Netherlands, and the US is 0.29–16.3 µg/m 3 . Mercury in some fly ash and gypsum, and in most WFGD and WESP wastewater, is higher than the relevant limits, which needs to be paid attention to during their processing. Mercury removal technologies for CFPPs can be divided into pre-combustion (including coal washing technology and mild pyrolysis method), in-combustion (including low-NOx combustion technology, circulating fluidized bed combustion technology, and halogens addition into coal), and post-combustion (including existing commercial SCR catalyst improvement, inhibiting Hg 0 re-emission in WFGD, mercury oxidizing catalysts, injecting oxidizing chemicals, carbon-based adsorbents, fly ash, calcium-based adsorbents, and mineral adsorbents) based on the mercury removal position. The mercury removal effects, mercury removal mechanism, and/or influencing factors are summarized in detail. One of the regenerable mercury removal adsorbents, the magnetic adsorbent modified by metal oxides or the metal halides, is the most promising sorbent for mercury removal from CFPPs. It has advantages of high mercury removal efficiency, low investment, easy separation from fly ash, and mercury recovery, etc. Lastly, further works about mercury transformation in coal combustion atmosphere, mercury co-removal by APCDs, the emission in CFPPs, and mercury removal technologies for CFPPs are noted.